TNFα Induces DNA and Histone Hypomethylation and Pulmonary Artery Smooth Muscle Cell Proliferation Partly via Excessive Superoxide Formation - Patrick Crosswhite; Zhongjie Sun (MDPI AG, 2024)
Objective: The level of tumor necrosis factor-α (TNF-α) is upregulated during the development of pulmonary vascular remodeling and pulmonary hypertension. A hallmark of pulmonary arterial (PA) remodeling is the excessive proliferation of PA smooth muscle cells (PASMCs). The purpose of this study is to investigate whether TNF-α induces PASMC proliferation and explore the potential mechanisms. Methods: PASMCs were isolated from 8-week-old male Sprague-Dawley rats and treated with 0, 20, or 200 ng/mL TNF-α for 24 or 48 h. After treatment, cell number, superoxide production, histone acetylation, DNA methylation, and histone methylation were assessed. Results: TNF-α treatment increased NADPH oxidase activity, superoxide production, and cell numbers compared to untreated controls. TNF-α-induced PASMC proliferation was rescued by a superoxide dismutase mimetic tempol. TNF-α treatment did not affect histone acetylation at either dose but did significantly decrease DNA methylation. DNA methyltransferase 1 activity was unchanged by TNF-α treatment. Further investigation using QRT-RT-PCR revealed that GADD45-α, a potential mediator of DNA demethylation, was increased after TNF-α treatment. RNAi inhibition of GADD45-α alone increased DNA methylation. TNF-α impaired the epigenetic mechanism leading to DNA hypomethylation, which can be abolished by a superoxide scavenger tempol. TNF-α treatment also decreased H3-K4 methylation. TNF-α-induced PASMC proliferation may involve the H3-K4 demethylase enzyme, lysine-specific demethylase 1 (LSD1). Conclusions: TNF-α-induced PASMC proliferation may be partly associated with excessive superoxide formation and histone and DNA methylation.